ERC Decision of 29 November 1999 on Exemption from Individual Licensing of Receive Only Earth Stations (ROES) (CEPT/ERC/DEC/(99)26) - Stéphan le Goueff (Satellite Regulation in Europe, 2000)
Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors derived from chromaffin cells of the adrenal medulla and extra-adrenal paraganglia. Over the past two decades, the genomic characterization of PPGLs has profoundly transformed their diagnosis, classification, risk stratification, and therapeutic management. Up to 40% of PPGLs harbor germline pathogenic variants, the highest proportion among human neoplasms, and somatic driver events are identified in a substantial fraction of the remaining cases. Integrative multi-omic studies have established three main molecular clusters: a pseudohypoxic cluster driven by Krebs-cycle alterations (SDHx, FH, MDH2, DLST) and HIF-2α pathway alterations (VHL, EPAS1, EGLN1/2); a kinase-signaling cluster driven by activation of RAS/MAPK and PI3K/AKT pathways (RET, NF1, HRAS, TMEM127, MAX); and a Wnt-signaling cluster characterized primarily by MAML3 fusions. This review summarizes progress in PPGL genomics, highlighting geographic and sex-related particularities. Using EPAS1/HIF-2α and RET as paradigmatic examples, we illustrate how diverse germline, somatic, mosaic, and fusion events converge on common core signaling hubs that can be therapeutically exploited with FDA-approved selective inhibitors for relevant targets (i.e., belzutifan for HIF-2α; selpercatinib and pralsetinib for RET). We further review the genomic determinants of metastatic risk (SDHB, ATRX, TERT, MAML3 fusions), the immune microenvironment of metastatic disease, and emerging radionuclide theranostic, liquid biopsy biomarkers, and integrative multi-omic approaches, that are reshaping precision medicine for PPGLs.